Characterization of an unidentified Sarcocystis falcatula-like parasite from the South American opossum, Didelphis albiventris from Brazil - Dubey, J. P.; Lindsay, D. S.; Rezende, PCB; Costa, A. J. (Soc Protozoologists, 2000)
An unidentified isolate of a Sarcocystis falcatula-like parasite was obtained from the lungs of budgerigars (Melopsittacus undulatus) fed sporocysts from a naturally-infected South American opossum, Didelphis albiventris from Brazil. Four captive budgerigars fed sporocysts from the opossum intestine died of acute sarcocystosis 8, 10, and 12 days after oral inoculation (DAI); one budgerigar was killed 12 DAI when it was lethargic. Schizonts and merozoites found in the lungs of the budgerigars reacted mildly with polyclonal S. falcatula antibody. The parasite was isolated in equine kidney cell cultures inoculated with lung tissue from a budgerigar that was killed 12 DAI. Two budgerigars inoculated subcutaneously with 100,000 culture-derived S. falcatula merozoites developed acute sarcocystosis and S. falcatula-like schizonts were found in their lungs 15 and 16 DAI. Four budgerigars kept as unfed controls in the same environment remained free of Sarcocystis infection. The parasite underwent schizogony in African green monkey kidney cells and bovine turbinate cells. Merozoites divided by endopolygeny, often leaving a residual body. Polymerase chain reaction studies using primers JNB33/JNB54 and Hinf I and Dra I digestion indicated that the isolate was not S. falcatula. Results of this study indicated that the South American opossum, D. albiventris, is a definitive host for yet another S. falcatula-like parasite.
Keywords: budgerigars; cell culture; development; polymerase chain reaction; schizonts